Percepção de suporte familiar no programa atitude e as implicações na assistência aos usuários de crack - Carvalho, Michelle Maria Campos (2016)
Crack usage has constituted a public health problem by the various individual, family and social consequences it causes. The aim of this study is to investigate the relationship between family support perspective of crack users, family and social technicians from the ATTITUDE program, analyzing the possible implications of these perceptions on the assistance for users and their families. We chose to develop the thesis in the format of articles. In the first article, we reviewed narratives based on 23 articles surveyed in the VHL databases Scielo Journals and Science Direct, in order to assess the contributions of these studies to public coping strategies with crack. The criteria adopted for the selection of items were: 1) articles on "crack and public policy," published in the last five years, and 2) studies with the population or on the Brazilian public policy. As a result, it was included nine epidemiological articles, three on clinical drug, three on contexts of use and violence, seven on social representation and media and one about family. Aspects such as change in Community assistance, intersectional policies, surveillance and epidemiological control, better integration between organizations working to reduce demand and increase in clinical research, were highlighted as important in proposing public policies. The second article is an answer to the main objective of the study, being conducted with 62 participants. Initially, it was applied to 46 crack users, linked to the Program ATTITUDE. Inventory of Family Support Perception (ISPF), which showed a high internal consistency (α = 0.88). In the second phase, a semi-structured interview with eight selected users was conducted between the 46 initial four families and 12 social workers program. The average age of these users was 30 years (SD = 6.98), whose socio-demographic profile refers to users, mostly: not married (78.3%), who lived alone (52.2%), with incomplete primary education (63%) coming from families without coexistence between parents (65.2%) who responded to the IPSF with reference to the family of origin (87%). Significant correlations were found between living alone and having a low perception of family support (r = 0.324; p = 0.05). The factor analysis also showed a significant correlation between Factor 1 (affective-consistent), and family (r = 0.460; p = 0.01) and with whom resides (r = 0.309; p = 0.05). In the qualitative stage, a content analysis was performed, revealing themselves, in general, four main themes for users and families, such as: family influence, family relationships, dealing with problems and expression of feelings. For technicians, four other themes were identified: family contribution, therapeutic activities, approach to family and experience report. The predominance of the perception of a low family support (t (44) = -4.428, p <0.05), as evidenced in the quantitative analysis, was consonant with the speech of the other participants during the interview. In line with the literature, this study also found the prevalence of maternal support and peer influence overlapping the family s as observed in the link of users with crack. It is argued in the light of Social Cognitive Theory, the influence family self-efficacy and social modeling have on substance use. This reflection reveals the importance of executing a proposition already included in the National Policy for Social Assistance, which refers to a more systemic view on the issue of crack consumption, covering both user needs and their families. It is believed that the paradigms can be improved in order to encourage new policy models in the care of drug users, especially crack.